Deriving and Using Descriptors of Elementary Functions in Rational Protein Design - Yin, Melvin; Goncearenco, Alexander; Berezovsky, Igor N. (Frontiers in Bioinformatics, 2021)
Rational design of proteins with desired functions requires a comprehensive description of the functional building blocks. The evolutionary conserved functional units constitute nature's toolbox; however, they are not readily available to protein designers. This work focuses on protein units of subdomain size that possess structural properties and amino acid residues sufficient to carry out elementary reactions in the catalytic mechanisms. The interactions within such elementary functional loops and the interactions with the surrounding protein scaffold constitute the descriptor of elementary function. The computational approach to deriving descriptors directly from protein sequences and structures and applying them in rational design is implemented in a proof-of-concept DEFINED-PROTEINS software package. Once the descriptor is obtained, the elementary functional loop can be fitted into existing or novel scaffolds to obtain desired function. For instance, descriptor may be used to determine the necessary spatial restraints in a fragment-based grafting protocol. We illustrate the approach by applying it to well-known cases of elementary functional loops including phosphate-binding P-loop, diphosphate-binding glycine-rich motif, and calcium-binding EF-hand motif, which could be used as jump-starting templates for user applications. The package is freely available at: https://github.com/MelvinYin/Defined_Proteins.